Anthropology. Correspondence Re., Cameroon Province (Colonial Letters and the Contact of Knowledges, 1949)
This file contains colonial Anthropology by Dr. Phyles Kabery and correspondences
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies